Argyreia speciosa attenuates streptozotocine-nicotinamide-induced hyperglycemia in experimental animals of type-2 diabetes mellitus - Nandi M.K.; Garabadu D.; Krishnamurthy S.; Singh T.D.; Singh V.P. (My University, 2025)
Argyreia speciosa (AS; Family: Convolvulaceae) is known for its anti-diabetic activity in traditional medicine system and is validated in ethnopharmacological studies. However, there is no report till date based on hypoglycemic activity of leave extract of this plant. Hence, the present study explores the anti-hyperglycemic potential of methanolic extract of AS (MAS) in a rat model of type-2 diabetes mellitus (T2DM). T2DM was induced in male rats by a single injection of streptozotocin, 15 min after nicotinamide administration. MAS at highest dose level attenuated the plasma glucose level in rats subjected to glucose load similar to that of metformin. Moreover, both dose of MAS reduced plasma glucose level in normal rats. MAS (400 mg/kg) significantly attenuated the plasma glucose level in T2DM rats. Further, MAS at highest dose level attenuated T2DM-induced increase in the level of total cholesterol, triglyceride and low density lipoprotein, and decrease in the level of high density lipoprotein in the plasma of the rats. MAS (400 mg/kg) attenuated the T2DM-induced increase in the level of lipid peroxidation and decrease in the activities of superoxide dismutase and catalase in both plasma and liver tissues. In addition, MAS at highest dose level improved the T2DM-induced decrease in the level of expression of GLUT-4 in the liver. These results collectively indicate that the anti-hyperglycemic activity of MAS against T2DM condition could be due to the improvement in the aberrant lipid profile, oxidative stress and insulin sensitivity. Hence, MSG could be a potential therapeutic option in the management of T2DM.